2020
DOI: 10.1186/s12887-020-02285-5
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte ratio and scoring system for predicting coronary artery lesions of Kawasaki disease

Abstract: Background: Kawasaki disease (KD) causes coronary artery lesions (CAL) and is the leading cause of acquired heart disease in children. The aim of this study is to evaluate the risk factors and setup a scoring system for predicting CAL of KD. Methods: We retrospectively reviewed a total of 478 patients diagnosed with KD. We compared age, gender, laboratory data, and treatment response in two groups and developed a scoring system for predicting CAL. Results: During the study period, 365 of these patients had com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
42
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 43 publications
6
42
2
Order By: Relevance
“…In our case, we found that these two neutrophil markers are elevated by 58 and 48 folds in KD neutrophil compared to healthy control respectively, which is a strong evidence that neutrophil induced immune disorder existed in KD patient. Neutrophil to leukocyte ratio is a severity marker for KD [26], for further study, we can explore more cases and validate the neutrophil activation pattern stability in KD.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, we found that these two neutrophil markers are elevated by 58 and 48 folds in KD neutrophil compared to healthy control respectively, which is a strong evidence that neutrophil induced immune disorder existed in KD patient. Neutrophil to leukocyte ratio is a severity marker for KD [26], for further study, we can explore more cases and validate the neutrophil activation pattern stability in KD.…”
Section: Discussionmentioning
confidence: 99%
“…KD as one of the most common autoimmune vasculitis in children also showed abnormally increased neutrophils in varying degrees in the acute stage in our present study. It was widely considered that increased neutrophils played a pivotal role in KD, especially in IVIG resistance (8,9) and CALs formations (14,15), although the precise mechanisms were unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic meta-analysis review, the neutrophil to lymphocyte ratio (NLR) was shown as an independent risk factor of initial IVIG resistance in KD ( 36 ). However, recent studies have indicated that the predictive value of NLR alone was not good enough to determine IVIG resistance and CAL formation in KD ( 37 , 38 ). We supposed that the neutrophil percentage of peripheral WBCs may play a role in this study.…”
Section: Discussionmentioning
confidence: 99%